核桃内源性多酚的体外抗氧化能力及对核桃油 氧化稳定性的影响In vitro antioxidant capacity of endogenous walnut polyphenols and their effects on the oxidation stability of walnut oil - 杜伊晗，王书语，向燕，邓莎，何贵萍，何强，董怡 DU Yihan, WANG Shuyu, XIANG Yan, DENG Sha, HE Guiping, HE Qiang, DONG Yi (Zhongguo youzhi, 2024)
为促进核桃加工副产物的综合利用，探究副产物中多酚对核桃油氧化稳定性的影响，测定了槲皮素、没食子酸、儿茶素、绿原酸、鞣花酸5种核桃内源性多酚对DPPH和ABTS+自由基的清除能力及氧自由基吸收能力（ORAC）以评价其体外抗氧化能力，并将5种内源性多酚分别加入核桃油中，进行18 d的加速氧化试验，以酸值、过氧化值、共轭二烯值、共轭三烯值、同步荧光光谱、色泽及感官品质（透明度、气味、滋味）作为考察指标，分析其对核桃油氧化稳定性的影响。结果表明：槲皮素、没食子酸和绿原酸的体外抗氧化能力较强；5种多酚均能有效减缓核桃油酸值、过氧化值、共轭二烯值和共轭三烯值的升高，其中没食子酸、绿原酸和儿茶素在维持核桃油感官品质方面优于其他2种多酚。综上，在开发核桃油相关产品时，可以考虑通过添加没食子酸、儿茶素和绿原酸提高产品的氧化稳定性。To promote the comprehensive utilization of the walnut processing by-products and explore the effect of polyphenols from the by-products on the oxidation stability of walnut oil, the DPPH and ABTS+ radical scavenging activities and oxygen radical absorption capacity (ORAC) of five walnut endogenous polyphenols including quercetin, gallic acid, catechin, chlorogenic acid and ellagic acid were measured to analyse their in vitro antioxidant capacity. To compare and analyse the effect of the five walnut endogenous polyphenols on walnut oil′s oxidation stability, acid value, peroxide value, conjugated diene value, conjugated triene value, synchronous fluorescence spectra, color and sensory index (transparency, odours, taste) of walnut oil added with five endogenous polyphenols were determined during the 18 d accelerated oxidation experiment. The results showed that in vitro antioxidant capacities of quercetin, gallic acid and chlorogenic acid were stronger. All five polyphenols could effectively inhibit the increase of acid value, peroxide value, conjugated diene value and conjugated triene value, among which gallic acid, catechin and chlorogenic acid were superior to the other two polyphenols in maintaining the sensory quality of walnut oil. Therefore, when developing walnut oil related products, it can be considered to improve the oxidation stability of products by adding gallic acid, chlorogenic acid and catechin.